MoSe2 and NiCo2O4/NiO Based HybridNanostructure as Novel Electrocatalyst for High Performance Rechargeable Zinc-Air Battery - Maurya P.K.; Mishra S.; Mishra A.K. (My University, 2025)
Efficient air electrocatalysts are needed to develop eco-friendly rechargeable Zinc-air (Zn-air) batteries for renewable energy storage. Here, we investigate the electrocatalytic activity of hydrothermally synthesized MoSe2, NiCo2O4/NiO and NiCo2O4/NiO-MoSe2 hybrid nanostructure by performing oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) studies. The NiCo2O4/NiO-MoSe2 hybrid nanostructure (Tafel slope∼ 54 mV decade−1) shows best electrocatalytic activity and stability for OER study among synthesized electrocatalysts. Further, the oxygen reduction behaviors of prepared catalysts have been observed in oxygen saturated electrolyte solution. The excellent electrocatalytic activity of hybrid nanostructure can be associated with its high electrochemical active surface area, number of active sites and possibly due to the presence of selenium vacancies and edges in MoSe2. Furthermore, we demonstrate Zn-air batteries with these electrocatalysts as air cathode, showing open circuit potential of 1.42 V, the specific capacity of 1023 mA h gZn−1 and energy density of 1195 W h kgZn−1, with high durability for hybrid nanostructure-based Zn-air battery. To the best of our knowledge, this is the first study demonstrating pristine MoSe2 and NiCo2O4/NiO-MoSe2 hybrid nanostructure-based cathodes for Zn-air batteries with excellent specific capacity and energy density. © 2022